(untitled) (Indonesian Journal of Civil Engineering Study, 2026)
Roads are vital infrastructure in the land transportation system, playing a crucial role in supporting public mobility and the smooth distribution of goods and services. Good road quality is an important indicator of economic growth, regional connectivity, and equitable national development. However, over time and with high traffic intensity, road pavement conditions tend to gradually degrade. Factors such as extreme weather, poor drainage, low-quality materials, and non-compliance with technical specifications during construction and maintenance processes contribute to accelerating structural and functional damage. One of the affected road sections is the Kudus East Ring Road, which plays a strategic role in connecting industrial areas, residential areas, public facilities, and economic centers in Kudus Regency and its surroundings. This study aims to analyze the level of pavement damage on this section and determine its priority for treatment using two approaches: the Bina Marga method and the Surface Distress Index (SDI). The Bina Marga method classifies road conditions based on visual observation of the type and severity of damage, then determines the Priority Order (UP) as a reference in providing recommendations for periodic and routine maintenance actions. Meanwhile, the SDI method uses a quantitative approach by considering parameters such as the percentage of crack area, crack depth, and the number of holes, and the depth of wheel grooves, which are converted into an SDI score. Comparison of research results shows that the level of damage to the Kudus East Ring Road at STA 1+800 to 3+800 with the Bina Marga method is mostly categorized as light to moderate damage with UP 4-6, while the results of research with the SDI method at STA 1+800 to 3+800 show that the level of damage is mostly categorized as good with an SDI value of 15. This discrepancy reflects the differences in approach and sensitivity between the two methods in assessing road damage.